Cross-sectional properties of complex composite beams - Mohd Yassin, Airil Y.; Nethercot, David A. (Elsevier Ltd, 2007)
A procedure is presented for the calculation of the key cross-sectional properties of steel–concrete composite beams of complex cross-section. The novel feature of the procedure is the use of functions to describe the shape of the different elements in a cross-section; this permits determination of the cross-sectional properties through appropriate integrations. The formulation is developed in a format that is directly suitable for computer programming, i.e. in matrix forms and operations. It is completely general in terms of the shape of the cross-section. The procedure is applied to a new type of composite beam known as the PCFC (pre-cast cold-formed composite) beam, details of which are explained herein. This is shown to perform better than equivalent, more conventional composite beams at the ultimate condition, but is slightly less efficient when considering some serviceability aspects.